PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DI RSUD SUKOHARJO - DWI HARYANTI; ENDANG WINARSIH; NGAISAH NGAISAH (JURNAL WIRANOMIKA, 2024)
The formulation of the problem in this study is whether there is a partial influence of Organizational Culture (X1), Work Environment (X2) and Work Discipline (X3) and Compensation (X4) on Employee Performance (Y) in RSUD Sukoharjo? Is there a simultaneous influence Organizational Culture (X1), Work Environment (X2) and Work Discipline (X3) And Compensation (X4) on Employee Performance (Y) Sukoharjo Hospital? Of the four variables, which variable most dominantly influences Sukoharjo Hospital Employee Performance (Y) RSUD Sukoharjo?. This study aims to determine the partial influence of Organizational Culture (X1), Work Environment (X2) and Work Discipline (X3) and Compensation (X4) on Employee Performance (Y) in Sukoharjo Hospital. Knowing the simultaneous Influence of Organizational Culture (X1), Environment Work (X2) and Work Discipline (X3) and Compensation (X4) on Employee Performance (Y) at RSUD Sukoharjo. Knowing the most dominant variable affecting the Employee Performance at RSUD Sukoharjo (Y) RSUD Sukoharjo.